Prof. Rolf F. Barth: the future of boron neutron capture therapy will depend on the clinical trials of accelerator-based boron neutron capture therapy - Yu, Tan-Lun (Therapeutic Radiology and Oncology, 2018)
The 18thInternational Congress on Neutron Capture Therapy was held successfully at theChang Yung-Fa International Convention Center in Taipei, Taiwan from October 28thto November 2nd, 2018. The theme of the 18th Congress is“Precision Therapy, Beautiful Tomorrow—We Here, We Care.” This congressgathered international clinicians and researchers from academia and industry toshare their findings and generate new thoughts and discoveries related to boronneutron capture therapy (BNCT). The key areas included recent clinical results,the latest development in accelerator-based neutron sources, the nextgeneration of boron-10 delivery agents, as well as progress in chemical and biologicalresearch.